POTENSI PENDIRIAN BMT DI KECAMATAN SUNGAI AUR KABUPATEN PASAMAN BARAT - Wira, Ahmad; Septia, Septia (JURIS (Jurnal Ilmiah Syariah), 2015)
Sungai Aur (Sumatera Barat) has its own values and tradition that promote the spirit of togetherness in any aspects of life. These, in turn, will encourage the growth and development of Islamic financial institutions in this region well. The data were analyzed by employing descriptive and SWOT analyses methods. Descriptive analysis was conducted by describing the result of the survey gathered through questionnaire while the SWOT one dealt with analyzing both internal and external conditions of the organization as the basis for designing strategies and work plans. From those analyses it can be figured out those which were potentially strengths, weaknesses, opportunities and threats of the region.Kata kunci: potensi, BMT, Sungai Aur